Friend strain of spleen focus-forming virus is a recombinant between ecotropic murine type C virus and the env gene region of xenotropic type C virus. - Troxler, D H (1977)
The spleen focus-forming virus (SFFV), a replication-defective murine leukemia virus that causes the rapid transformation of certain hematopoietic target cells, has acquired specific xenotropic viral genetic information not contained in Friend helper virus. In the current studies, it is shown that a cDNA that represents a xenotropic virus portion of SFFV detects genetic sequences derived from the env gene region of murine xenotropic virus. The significance of the acquisition of these xenotropic viral sequences by SFFV is discussed with regard to their possible role in the rapid leukemogenicity of SFFV, and an analogy is drawn between the formation of SFFV and the formation of the Kirsten and Harvey sarcoma viruses.